Making a collection count : a holistic approach to library collection management - Hibner, Holly (Chandos information professional series, 2010)
Takes a uniquely holistic and comprehensive approach to helping public, academic, school, and special librarians develop collections that are functional, up-to-date, and relevant. The authors focus specifically on collection quality, and provide highly practical guidance for selection, cataloging, shelving, circulation, staff management, budgeting, and weeding.